Governance and Policy Analysis of Indonesia’s Prospective BRICS Membership for Expanding Global Market Access - Riady Ibnu Khaldun; Rezky Ramadhan Antuli; Asma Amin (Pusat Studi Pembangunan dan Pemberdayaan, 2026)
This study is based on the changing global economic landscape, which is increasingly moving toward the dominance of developing countries, as well as the need for Indonesia to diversify its trade and investment partners amid global economic uncertainty. The research aims to analyze Indonesia’s potential membership in the BRICS group of countries (Brazil, Russia, India, China, and South Africa) as a strategy to expand access to global markets. Using a qualitative-descriptive approach and literature analysis, this study evaluates various factors that support Indonesia’s eligibility to join BRICS, including macroeconomic aspects, geostrategic position, and commitment to South-South cooperation. The findings show that Indonesia has considerable potential to join BRICS in terms of economic capacity, regional influence, and available resources. Membership in BRICS is considered to offer strategic benefits in the form of access to new global markets as well as potential investment development from member countries.